Contents tourism and local community revitalization: the case of Hida-Furukawa as an anime sacred site for 'Your Name' - Reyes, Maria Corazon C.
Amidst Japan's population and labor dilemma, tourism became a significant resource to help revitalize its economy. Japan is a tourism nation, capitalizing on its cultural industry and large consumer market. Under the concept of content-induced tourism, a specific phenomenon of anime tourism is recognized and embodied in national economic policymaking, mainly touted in the "Cool Japan Strategy". Today, Japan's tourism in major cities has considerably developed, but the impact of tourism in the rural setting is relatively understudied.